2015
DOI: 10.1007/s00246-015-1216-3
|View full text |Cite
|
Sign up to set email alerts
|

Total Energy Expenditure of Infants with Congenital Heart Disease Who Have Undergone Surgical Intervention

Abstract: Growth failure is often observed in infants with congenital heart disease (CHD); it is unclear, however, whether growth failure is due to increased total energy expenditure (TEE). An observational study of infants with CHD and surgical intervention within the first 30 days of life and healthy infants of similar age was undertaken. TEE was measured using the doubly labeled water method in 3-month-old infants (n = 15 CHD, 12 healthy) and 12-month-old infants (n = 11 CHD, 12 healthy). Multiple linear regression m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 46 publications
(78 reference statements)
0
23
0
Order By: Relevance
“…Additionally, a more general goal in cardiologic interventions and surgical procedures is to optimize the energetical state of the heart muscle allowing the most efficient oxygen consumption of the myocardial tissue. This goal can usually be reached by optimization of the hemodynamic situation [35]. However, in patients with CoA, even years after successful treatment of the narrowing, increased morbidity and mortality have remained major issues.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a more general goal in cardiologic interventions and surgical procedures is to optimize the energetical state of the heart muscle allowing the most efficient oxygen consumption of the myocardial tissue. This goal can usually be reached by optimization of the hemodynamic situation [35]. However, in patients with CoA, even years after successful treatment of the narrowing, increased morbidity and mortality have remained major issues.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, with improved surgical and catheter‐based interventions, intensive care, imaging, medical therapies, and specialty teams trained to manage HF in children, survival rates have improved . Care has shifted from focusing on survival to optimizing quality of life and health outcomes, such as nutrition status . Appropriate growth in well children is considered an important indicator of health.…”
mentioning
confidence: 99%
“…1 Care has shifted from focusing on survival to optimizing quality of life and health outcomes, such as nutrition status. 5 Appropriate growth in well children is considered an important indicator of health. In the context of HF, appropriate growth may indicate control of HF symptoms.…”
mentioning
confidence: 99%
“…Due to this complex milieu, there is no consensus on the ideal equation for estimating REE in pediatric patients following CPB. Existing studies have shown poor performance of these estimates overall …”
Section: Introductionmentioning
confidence: 99%
“…Existing studies have shown poor performance of these estimates overall. 12 In this study, the utility of a novel method of estimating REE is assessed compared with gold standard indirect calorimetry in a cohort of critically ill children following CPB. An additional objective of this study was to perform a comparative analysis of the accuracy of this novel methodology relative to other currently used clinical equations with reference to indirect calorimetry measurement.…”
Section: Introductionmentioning
confidence: 99%